PERSEPSI PETANI TERHADAP UPJA (USAHA PELAYANAN JASA ALSINTAN) DI KECAMATAN TAWANGSARI KABUPATEN SUKOHARJO - Listya Gustani Husnayati; Suwarto Suwarto; Hanifah Ihsaniyati (AGRITEXTS: Journal of Agricultural Extension, 2018)
The aim of this research is to know the peasants’ perception factors to UPJA, to analyze the peasants’ perception to UPJA, to analyze the correlation between the peasants’ perception maker with the peasants’ perception to UPJA, and to analyze the difference of the peasants’ perception to UPJA based on the farmers area and peasants’ position in the peasants’ group. The basic method used in this research was descriptive quantitative with survey technique. The location of the research was determined by the purposive that was in Tawangsari District Sukoharjo Regency, by taking 2 peasants’ group that was Ngudi Rejeki in Dalangan and Ngudi Makmur in Majasto Village. The sample was determined by multistage cluster random sampling technique, as many as 60 farmer’s respondents. The data analysis used was rank spearman  and  U  Mann-Whitney.  The  result  of  this  research  indicate  that  the perception form factor was the age of the farmers in the medium category, formal education in the high category, non-formal education in the low category, experience in the medium category, income in the very high category, wide land in the very broad categories and the economic environment in the medium category. The Peasants’ Perception to UPJA that was 61.67% farmer’s respondents had the good perception to UPJA.  There  was  a  significant  relation  between  non-formal  education  and  the economic environment with peasants’ perception to UPJA at 99% level of confidence, at 90% level there was a significant relation between the experience, income and land area with the peasants’ perception to UPJA, while the age and formal education there was no significant correlation with the farmers perception to UPJA. There was a significant difference perception to UPJA based on peasants’ area and peasants’ position in peasants’ group.